Evaluation of salt tolerant mungbean (Vigna radiata L.) Genotypes on growth through bio-molecular approaches (Bangladesh Journal of Agricultural Research, 2019)
This study was conducted to obtain saline tolerant mungbean genotypes through evaluating growth, biochemical and molecular parameters, and possible salt tolerant mechanisms were studied in different salt sensitive genotypes. Thirteen prescreened mungbean genotypes were grown on 0, 40, 80 and 120 mMNaCl induced salinity and evaluated by germination percentage, shoot and root length, superoxide (O2•-) generation rate, concentration of H2O2, lipid peroxidation (as malondialdehyde, MDA), methylglyoxal (MG), K+/Na+ and proline content in leaves. Based on these parameters, genotypes BD-10588, BD-6894 and IR-01 were selected as tolerant genotypes. For studying oxidative stress tolerance mechanism, BD-10588 and IR-01 were used as tolerant and BD-6887 and BD-10741 as susceptible genotypes, and comparative ROS (O2•- and H2O2), and MDA as well as LOX activity between the two groups were determined. Analysis of activities of ROS metabolizing antioxidant enzymes strongly suggested that superoxide dismutase in tolerant genotypes provided first line protection from salt induced O2•-. Higher catalase (CAT) and ascorbate peroxidase (APX) played major role in H2O2 metabolism in tolerant genotypes. Both specific and in-gel activities of glutathione peroxidase (GPX) strongly proved the H2O2 metabolism for reducing oxidative damage in both tolerant and susceptible genotypes. However, higher peroxidase activity was important for mitigating salt stress in susceptible mungbean genotypes. Therefore, SOD, APX and GPX are very important for protecting salt mediated oxidative damage in mungbean genotype.Bangladesh J. Agril. Res. 44(3): 469-492, September 2019